ON THE REFLECTION OF THE LIFESTYLE OF THE MIDDLE SANGZOR OASIS POPULATION IN HISTORICAL WRITTEN SOURCES - Sh.S.Achilov (Bright Mind Publishing, 2025)
In this article, the author tried to shed light on the fact that the study of the historical foundations of cattle breeding, which has a unique place in the daily life of the people of Jizzakh, especially the Middle Sangzor oasis, is one of the topical issues of historical science today, that the Middle Sangzor oasis, like other historical and ethnographic regions of Uzbekistan, is a unique, important micro-ethnographic region, and that the favorable geographical location of the oasis was formed by the combination of very different cultures and traditions, based on historical sources.
Keywords: Ustrushona, Middle Sangzar, Morguzar, Nurota, Avesta, Yaksart, Kangha, Herodotus, Ilonutti Gorge, Khaliliya, Dizak, Pshagor, Zamin, Yam. Abdullakhan II, Ubaidulla-noma, Yangi Kurgan.